198k views
20 votes
Substitution method
4x + y = 14
6x - 3y = 3​

User Adolfo
by
5.0k points

1 Answer

10 votes

Answer:

  • x = 2.5
  • y = 4

Explanation:

We know that:

  • 4x + y = 14
  • 6x - 3y = 3

Let's first solve for y by choosing any equation.

  • 4x + y = 14
  • => y = 14 - 4x

Now, let's substitute the value of y into the second equation.

  • 6x - 3y = 3
  • => 6x - 3(14 - 4x) = 3
  • => 6x - 42 + 12x = 3
  • => 18x - 42 = 3
  • => 18x = 42 + 3
  • => 18x = 45
  • => x = 45/18 = 5/2 = 2.5

Now, let's substitute the value of x into the equation of y.

  • => 14 - 4x = y
  • => 14 - 4(2.5) = y
  • => 14 - 10 = y
  • => y = 4

Hence, the value of x and y are 2.5 and 4 respectively.

User Metablaster
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.